A magnetic field sensor based on a dual S-tapered multimode fiber interferometer. (25th May 2018) - Zhang, Xu; Liu, Bo; Zhang, Hao; Wu, Jixuan; Song, Binbin; Wang, Chao
Abstract: A multimode interferometer (MMI) for the measurement of a magnetic field based on concatenated S-tapered fibers is proposed and experimentally demonstrated. Spectrally interrogated magnetic field sensing is achieved by integrating the proposed MMI with magnetic fluids. The magnetic sensitivity of the MMI reaches 0.011 dB Oe −1 . Owing to its desirable advantages such as compactness, low cost, fast response and flexible structure, the proposed MMI is anticipated to find potential applications in in situ measurements of the magnetic field.